PENANGANAN dan pengolahan baby fish nila / Th. Dwi Suryaningrum...[et.al]; editor, Febriani Ai Nurrohmah - Dwi Suryaningrum, Th. 1956-; Febriani Ai Nurrohmah (Penebar Swadaya, 2016)
76 hlm. : ilus. ; 23 cm.